2015
DOI: 10.1371/journal.pone.0139668
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Genome Characterization of the First Sicinivirus Isolate from Chickens in Mainland China by Using Viral Metagenomics

Abstract: Unlike traditional virus isolation and sequencing approaches, sequence-independent amplification based viral metagenomics technique allows one to discover unexpected or novel viruses efficiently while bypassing culturing step. Here we report the discovery of the first Sicinivirus isolate (designated as strain JSY) of picornaviruses from commercial layer chickens in mainland China by using a viral metagenomics technique. This Sicinivirus isolate, which contains a whole genome of 9,797 nucleotides (nt) excluding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Previous metagenomic studies into the avian gut microbiome have identified multiple picornavirus species in disease-affected and healthy birds, findings which have been echoed in the present study. However, the pathogenic potential of these viruses in avian species remains relatively unknown due to the large amount of genetic variation observed among these viruses Farkas et al, 2012;Bullman et al, 2014;Zhou et al, 2015). In the present study picornaviruses were commonly found alongside the Astroviridae, Caliciviridae, Parvoviridae, and bacteriophage families (Table 1) and seem to be prevalent in growth-stunted birds.…”
Section: Rna Virome Analysismentioning
confidence: 53%
See 1 more Smart Citation
“…Previous metagenomic studies into the avian gut microbiome have identified multiple picornavirus species in disease-affected and healthy birds, findings which have been echoed in the present study. However, the pathogenic potential of these viruses in avian species remains relatively unknown due to the large amount of genetic variation observed among these viruses Farkas et al, 2012;Bullman et al, 2014;Zhou et al, 2015). In the present study picornaviruses were commonly found alongside the Astroviridae, Caliciviridae, Parvoviridae, and bacteriophage families (Table 1) and seem to be prevalent in growth-stunted birds.…”
Section: Rna Virome Analysismentioning
confidence: 53%
“…Within these genera, viral contigs showed similarity to multiple species such as chicken gallivirus 1 (Gallivirus), aichivirus C (Kobuvirus), and chicken megrivirus (Megrivirus). A total of 217 contigs characterized as unclassified Picornaviridae showed similarity to the species sicinivirus 1, a novel picornavirus isolated from commercial broiler chickens in Cork, Ireland (Bullman et al, 2014) and recently reported in mainland China (Zhou et al, 2015). Sicinivirus 1 contigs were almost exclusively associated with RSS-affected samples with only one sicinivirus 1 contig associated with unaffected sample VF14-181 A1.…”
Section: Rna Virome Analysismentioning
confidence: 79%
“…Bats have been used to put an upper limitin the hundreds of thousands − of the total number of eukaryotic viruses that remain to be discovered (Anthony et al, 2013). Other insect and arthropod aggregators such as spiders and birds have also yielded many new RNA virus species (Debat, 2017;Ducatez and Guérin, 2015;Shean et al, 2017;Zhou et al, 2015).…”
Section: Bat-guano Crazy About Samplingmentioning
confidence: 99%
“…The family comprises 47 genera, with 13 of these identified from avian species ( 1 3 ). Avian picornaviruses of the Sicinivirus genus have been identified in both healthy and diseased chickens, and the viruses’ role in disease remains unclear ( 4 9 ). Here, we report the sequences of five near-complete genomes of sicinivirus from North America.…”
Section: Announcementmentioning
confidence: 99%